PENGEMBANGAN BAHAN AJAR MATERI GEOMETRI BERORIENTASI KEMAMPUAN REPRESENTASI MATEMATIS - Hadi Nugroho; Rizki Wahyu Yunian Putra; Abi Fadila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research focuses on developing instructional materials oriented towards mathematical representation skills in solid geometry, aiming to evaluate their effectiveness and attractiveness to students. The study employs a Research and Development (R&D) approach using the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation phases. Data collection in this study involves both test and non-test techniques. A test was administered before and after using the instructional materials to compare students’ scores using the N-Gain test, while a non-test technique (questionnaire) was administered after the instructional materials were implemented to gather students’ responses. The final results of this research show that the instructional materials for solid geometry are valid (V = 3.28), highly attractive (M = 3.38), and sufficiently effective (criteria: the average posttest score is higher than the average pretest score, N-Gain = 0.38) in improving students’ mathematical representation skills.